2018
DOI: 10.1159/000489545
|View full text |Cite
|
Sign up to set email alerts
|

Differential Patterns of Secreted Frizzled-Related Protein 4 (SFRP4) in Adipocyte Differentiation: Adipose Depot Specificity

Abstract: Background/Aims: Secreted frizzled-related protein 4 (SFRP4) is a member of the SFRP family that acts as soluble modulators of Wnt signaling. Given the substantial rise in obesity, depot-specific fat accumulation and its associated diseases like diabetes, it is important to understand the molecular basis of depot-specific adipocyte differentiation. In the current study, we investigated the expression of SFRP4 in both subcutaneous and visceral adipose tissue in terms of their differentiation. Methods: White pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
0
16
0
3
Order By: Relevance
“…SFRP4 is a secretory protein with a size of 40 kDa, consisting of more than 300 amino acids (76). It can inhibit the activation of the Wnt signaling pathway by competitively binding with receptors related to the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SFRP4 is a secretory protein with a size of 40 kDa, consisting of more than 300 amino acids (76). It can inhibit the activation of the Wnt signaling pathway by competitively binding with receptors related to the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bioinformatics data analysis showed that the Secreted frizzled-related protein 4 promotes brown adipocyte differentiation expression level of SFRP4 in fat tissue of obese pigs was significantly higher compared with that of lean pigs (12). Thirdly, previously published research findings demonstrated that the expression pattern and function of SFRP4 has adipose tissue depot specificity in subcutaneous and visceral adipose tissue in mice (13). However, little is known about the role and function of SFRP4 in the formation and thermogenesis of BAT which plays an important role in lipid metabolism, obesity and energy consumption (4).…”
Section: Introductionmentioning
confidence: 90%
“…The number of transcripts was quantified, and each sample was normalized according to its b-actin content. Relative expression of the gene of interest (GOI) was determined using calculation=2 (Cq β-actin gene-Cq GOI) (13). PCR primer sequences are shown in Table SI.…”
Section: Reverse Transcription-quantitative (Rt-q)pcr Analysismentioning
confidence: 99%
“…It has been reported that SFRP4 is overexpressed during differentiation of preadipocytes to mature adipocytes as obese animals have more expression of SFRP4 as compared to lean animals . Differentiation of preadipocytes to adipose tissues in humans is affected by SFRP4 and SFRP4 overexpression leads to the elevation in lipid accumulation . The SFRP4 expression in adipose tissues of obese individuals was increased and is associated to insulin resistance …”
Section: Role Of Sfrp4 In Diabetes and Obesitymentioning
confidence: 99%
“…Adipogenesis is stimulated by SFRP1, SFRP2, and SFRP4 in both human and murine models . SFRP4 has been described to be involved in metabolism of glucose and lipids by interacting Wnt ligands and its level in obesity are increased . In undifferentiated cells, SFRP4 expression level is higher but with the progress of differentiation, its level is decreased.…”
Section: Role Of Sfrp4 In Diabetes and Obesitymentioning
confidence: 99%